(untitled) (Research, Society and Development, 2022)
The objective of this research was to gather information about the Brazilian scientific research with the macrofauna group of benthic invertebrates. The searches were carried out in the main databases of online scientific journals, such as: Science Direct, PubMed, Web of Science, Scopus, Scielo (Scientific Electronic Library Online), Capes Periodicals and Google Scholar, taking into account the studies carried out over the years. 10 years (2010 – 2020). The manuscripts were tabulated according to the following information: study region, environment in which the study was carried out (fresh, marine or estuarine), most cited macroinvertebrate phyla and the type of study performed (taxonomy, description of a group, diversity, between others). The South and Southeast regions are the ones with the most published works. The Principal Component Analysis (PCA) highlighted that Arthropoda is the taxon with the most records. Of the environments studied, the estuarine had the largest number of studies on Arthropoda in Brazil. In the researches analyzed, it was found that studies of distribution, characterization, diversity, description and composition predominate. The fact that the status of knowledge on benthic organisms is concentrated in the South and Southeast regions demonstrates that there is a deficit in studies of the benthic fauna in the other regions, demonstrating the need to expand the lines of research considering that the benthic fauna has great distribution in all Brazilian states and are important organisms because they have significant characteristics for the maintenance of the aquatic environment.